Alleviating health risks associated with rainwater harvesting. Issue 1 (31st March 2017) - Ward, Sarah; Butler, David; Daly, Bebhinn; Deegan, Ann Marie; Maganha de Almeida, Ana Carolina; Lennox, Iain
Abstract : Perceived and real public health risks associated with the quality of water from alternative water sources and supply systems, such as rainwater harvesting (RWH) and grey water reuse, continue to restrict their uptake in many countries. One option to alleviate these health risks is to treat alternative water to potable standard at the point of use (POU) as opposed to the point of supply, as undertaken in centralised systems. This paper presents the results of three international empirical field trials of a novel POU RWH treatment device. The results indicate that where the harvested rainwater did not contain elevated levels of pesticides or physico-chemical determinands, the POU device was able to reduce levels in outlet water to meet UK, EU and World Health Organization potable standards. Regarding microbiological determinands, such as total viable counts and coliforms, and microbial pathogens, such as Pseudomonas aeruginosa and Legionella spp., the device achieved reduction to potable standard and full pathogen removal, respectively. Thus, while it is possible to treat harvested rainwater to potable standard with a POU device, whether it is desirable to do so to alleviate risks for all end uses remains a question for further debate.